E-PARTISIPASI VIRTUAL DALAM SELAMATKAN LINGKUNGAN DI ERA DIGITAL - Kheyene Molekandella Boer (An-Nida : Jurnal Komunikasi Islam, 2019)
Issues about the environment often become the spotlight of the world, ranging from technological developments to a million environmental problems that never end. Now environmental issues are touched by the rapid development of digital technology. This makes a big change for the world of the environment. Ranging from digital conversations to top level or government decision-making to making environmental policies, all references are taken from community activities and participation that often voice their opinions on social media. Communication technology in the context of the environment that is most widely seen is the phenomenon of online petitions or known as "change.id". a site that offers space to discuss anything including environmental issues. The power of online petitions that move quickly by collecting votes through online signatures is able to stop the government's steps to dismantle Sophie's ship in Aceh. The reason is to save ecosystems such as long-developed coral reefs around the sophie ship that sank many years ago. E-participation as a form of digital democracy. Where the public is not obliged to appear physically in front of the government, through interactivity built in online media makes every active person involved without being limited by distance, space and time. Of course, with the concept of e-participation it is hoped that environmental issues can be controlled not only by the government but by the public. Because one indicator of the development of a country's progress is one of which is seen from the level of people's participation.